THE EFFECT OF GENOTYPES AND PARATYPE FACTORS ON COW PRODUCTIVITY - Ведмеденко, О. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The article deals with the study of the influence of paratype and genotypic factors on dairy productivity of cows under the conditions of Kherson region's economy. It was found that animals born in the fall had higher milk yields in the first, second and third lactations compared to peers born in other seasons, and amounted to 7967.4 kg, 85536.9 kg and 8868.6 kg, respectively. The predominance of autumn animals on milk yield, compared to those born in spring, was in the range of 4.1… 10.5%, in summer - 6.6… .11.1%. Analysis of one-factor complexes revealed a significant (P <0.01) force of influence of the season of birth and calving of first-borns on the milk yield and intensity of milk yield of the same level (6.00… .6.17%). The influence of other factors was significant and amounted to 93.8… 94.0%. The highest milk productivity was characterized by Holstein cows belonging to the Chif line. The average milk yield of the third lactation in the group of cows was 9954.5 kg, and exceeded that of other lines within this breed by 510.9… .363.2 kg (P <0.05). The largest difference in productivity of Holstein cow breed over the Ukrainian black and white breed was found among the animals of the Valiant line, which was higher by 1431.5 kg or 17.9%. The milk yield superiority of the different types of Starbak and Chifa breeds was 13.1% and 14.5% respectively. Regarding the Ukrainian black-and-white dairy breed, the lines tested were Chiff and Valiant, with yields of 8691.5 kg and 8012.1 kg, respectively. The two-factor ANOVA revealed that the rock factor had a vaild insignificant effect on the yield of 5.88% (P <0.01). The data from the analysis indicate that 90.6% of other factors are predominant